THE DUTCHS FLOATING LIFE ON DESHIMA ISLAND: A GLOOMY SIDE OF DUTCH-JAPAN RELATIONSHIP DURING THE TOKUGAWA PERIODE, 1715-1790 - Abdul Wahid (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2015)
In order to extend its trading network and engagement in the intra-Asian trading network, the VOC sought to gain contact with Japan, which was known for its luxurious products as copper and silk. At that time, Tokugawa Ieyasu just emerged as the new Japanese ruler, whose regime introduced a controversial policy known as Sakoku to cut Japan completely off from the international relations to strengthen internal politics. As a result, Japan lost its diplomatic and economic relationship with other nations. The Dutch (represented by the VOC) together with China and Korea - were the only exception as the Tokugawa regime granted them trading license and used them as window to see the outer worlds development. The VOCs offiers had to pay costly this privilege, however, since they should follow Tokugawas strict rules and control. They were allowed to settle and live only on a virtual island called Deshima, which was located on the bay of Nagasaki. Tokugawa regime provided all their needs, but restricted their movements and activities especially in accessing land and making contact with local inhabitants. Perusing the available printed historical sources to be combined with the recent literature, this paper describes the daily life of those VOCs Dutch offiers living on the island, and seeks to analyze the importance of this odd relations for political and economic relations of the two nations.Keywords: the VOC, Dutch, Tokugawa Japan, Deshima